Layer-by-layer hierarchically structured nanofibrous membrane scaffolds incorporating metal-organic framework and carbon nanotube adsorbents for high-performance versatile organic solvent recovery - Lim, Josh HuaiXun (2023)
Conventional organic solvent recovery is energy intensive and challenged by large footprint and complex operation and maintenance. To enable a more circular and sustainable pharmaceutical production, we amalgamate adsorption and membrane processes to address current Achilles heels in organic solvent recovery. In this work, we have successfully designed a polyacrylonitrile (PAN) electrospun membrane as scaffold to incorporate nanomaterial adsorbents in a layer-by-layer hierarchical structure. The porous nanofibrous morphology and layer-by-layer design, which deconstructs the adsorbent layers, help reduce the transport resistance of the isopropyl alcohol (IPA), leading to higher processing capacity at lower applied pressure, while maintaining the removal rates. To bring about versatility for different contaminants, we incorporated two different nanomaterials, namely positively charged metal-organic frameworks (MOFs), particularly MIL-101(Cr), and negatively charged functionalized multi-walled carbon nanotubes (MWCNTs) as powdered adsorbents, for the extraction of anionic and cationic dyes, respectively. Our results show that the MOF-based membrane scaffold can achieve 99% and 95% rose Bengal and methyl orange removal rates in IPA, respectively, while operating at a low operating pressure of 0.04 bar and delivering a processing capacity of 60 L m−2 h−1 of IPA, with good regeneration and recyclability of up to three cycles of removal process. On the other hand, the MWCNT-based membrane scaffold displays up to 90% methylene blue dye in IPA at 0.07 bar pressure and delivering a 40 L m−2 h−1 of IPA processing capacity in a single-cycle removal process. The promising recovery performance and facile tailoring of adsorbents to target contaminants of different charges render our adsorptive membrane scaffold process less energy intensive and highly versatile to meet various needs for solvent recovery in the pharmaceutical industry.